EXECUTIVES LEADERSHIP IN THE 21st CENTURE THAT AFFECTS THE TEAMWORK OF TEACHERS IN EDUCATIONAL INSTITUTIONS UNDER THE SURAT THANI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Yeejehsamah, Rodeemah; Nawakitpitoon, Nilrat; Chairoung, Noppharat (Journal of MCU Nakhondhat, 2023)
This research aims to: 1) Study of executive leadership in the 21th century 2) Study the teamwork of teachers in the school 3) Study the leadership of 21th century administrators that affect the teamwork of teachers in schools. Surat Thani Elementary School District 1 Office Research Format It is exploratory research (Survey Research) Samples used in this research namely Teachers affiliated with Surat Thani Elementary School District 1 for the academic year 2020 297 people the research showed that.1) The level of leadership of educational administrators in the 21 century Overall, it is at the highest level. 2) The level of teamwork of teachers in educational institutions. Surat Thani Primary Educational Service Area Office 1 found that the teamwork of teachers in educational institutions Communication Cooperation coordination creative thinking Continuous improvement Overall, it was at the highest level. 3) The relationship between 21 century executive leadership and the teamwork of teachers in educational institutions Affiliated with Surat Thani Elementary Education Area Office District 1 It was found that by executive leadership in the 21st century of executives in all aspects are visionary leadership Leadership with the art of leading Leadership that influences colleagues Ethical Leadership digital leader change leadership and teamwork of teachers in educational institutions. Communication Cooperation coordination creative thinking Continuous improvement It has a high (r=.832) correlation coefficient and a statistically significant correlation of the same direction at the level of .01.